Design Principles for Optimum Performance of Porous Carbons in Lithium–Sulfur Batteries. Issue 14 (2nd May 2016) - Sahore, Ritu; Levin, Barnaby D. A.; Pan, Mian; Muller, David A.; DiSalvo, Francis J.; Giannelis, Emmanuel P.
Abstract : A series of experiments is presented that establishes for the first time the role of some of the key design parameters of porous carbons including surface area, pore volume, and pore size on battery performance. A series of hierarchical porous carbons is used as a model system with an open, 3D, interconnected porous framework and highly controlled porosity. Specifically, carbons with surface areas ranging from ≈500–2800 m 2 g −1, pore volume from ≈0.6–5 cm 3 g −1, and pore size from micropores (≈1 nm) to large mesopores (≈30 nm) are synthesized and tested. At high sulfur loadings (≈80 wt% S), pore volume is more important than surface area with respect to sulfur utilization. Mesopore size, in the range tested, does not affect the sulfur utilization. No relationship between porosity and long‐term cycle life is observed. All systems fail after 200–300 cycles, which is likely due to the consumption of the LiNO3 additive over cycling. Moreover, cryo‐scanning transmission electron microscopy imaging of these carbon–sulfur composites combined with X‐ray diffraction (XRD) provides further insights into the effect of initial sulfur distribution on sulfur utilization while also revealing the inadequacy of the indirect characterization techniques alone in reliably predicting distribution of sulfur within porous carbon matrices. Abstract : Porosity characteristics of porous carbons toward their performance as sulfur hosts in Li–S battery cathodes are systematically investigated at a high sulfur loading of ≈80 wt%. A series of hierarchical porous carbons with highly controlled porosity is employed as a model system. Additionally, cryo‐TEM is used for the first time to directly observe the sulfur distribution in the composite particles.